Recycled Concrete Aggregates from Construction and Demolition Waste: A Systematic and Critical Review of a Sustainable Construction Material - Kanaujia, Subhas Chandra; Khan, Zishan Raza; Ahmad, Syed Aqeel; Singh, Vikash (International Journal of Environment, Engineering and Education, 2025)
The construction sector is a major consumer of natural aggregates and a significant contributor to carbon emissions. Recycled Concrete Aggregates (RCA), sourced from Construction and Demolition (C&D) waste, offer a sustainable alternative that supports circular economy principles. However, the inferior quality of RCA—mainly due to adhered mortar and weak interfacial transition zones (ITZs)—limits its structural application. This study aims to (1) systematically identify and classify RCA enhancement methods, (2) evaluate the impact of RCA on concrete performance, particularly strength and durability, and (3) highlight key barriers and opportunities for its broader implementation in structural concrete. A systematic review of 77 peer-reviewed articles published between 2000 and 2024 was conducted using PRISMA guidelines. The review analyzed diverse RCA treatment methods—mechanical, chemical, thermal, and biological—and their influence on concrete properties. Findings show that untreated RCA can reduce compressive strength by 10–30% and increase shrinkage by up to 50%. However, treatments such as acid soaking, mechanical polishing, and carbonation significantly improve RCA quality. When combined with supplementary cementitious materials (SCMs) and optimized mix design, treated RCA enables concrete to achieve comparable performance to conventional mixes. The technical viability of high-performance RAC is well supported by recent studies. The remaining challenges lie in standardization, quality control, and adoption at scale. This review concludes that while technical solutions are mature, the primary barrier to widespread adoption is the lack of integrated, performance-based regulatory frameworks, shifting the challenge from materials science to implementation science.